Anemia during pregnancy : a study in local district of Sarawak - Henry Sum Agong, Christina Busak (Faculty of Medicine & Health Sciences, 2008)
Anemia during pregnancy is a serious public health problem particularly in developing countries. This problem is not exceptional in Malaysia. However, there are limited data available to show the prevalence of anemia during pregnancy especially in the state of Sarawak. Most of the Malaysia's available data on anemia during pregnancy are based on data from West Malaysia. With the absence of data on anemia during pregnancy, it is difficult to evaluate intervention programs systematically. There is therefore, a need to study the magnitude of the problem locally as well to understand its epidemiology. This is a descriptive quantitative study conducted in Lawas District. Data collection was done from 23rd to 29th December 2007 and continued 4th till 8th February 2008. Triangulation method was used to enhance the findings of this study. Random sampling technique was used to select participants of this study. Five primary health care clinics were selected. A total of 80 antenatal mothers participated. This study highlighted several issues. Out of 80 participants 48.8% was identified to have anemia during pregnancy. The prevalence was highest among the Malays, Tagal followed by Lun Bawang, while chinese and Iban community being the least anemic. The highest prevalence group of anemia in pregnancy also reported among the grandmultiparas, third trimester, birth spacing between one to two years and mothers with low level of education. On the other hand, mother that had well balance diet on regular basis had the lowest prevalence of anemia. These findings are useful for Maternal Health Services to enhance health education.